Estudio de factibilidad para la constitución de una empresa relacionada con la elaboración de harina de banano en el cantón Pasaje provincia de el Oro - Vaca Andrade, Anggie Enith (2014)
The thesis is based on establishing the profitability of a farm for the manufacture of banana flour, which required the design of a dehydration plant banana for which specific targets, which determined settled: Execute market research, social, environmental and financial order to demonstrate how the project is feasible; Designing a national manufacturing processing plant, with the purpose to develop the product and; Payback was incurred to establish the project in the medium and long term. Continuous production of 22.7 tons of flour with good organoleptic properties is necessary. The Government will invest $ 2 million in equipment and machinery in the province of El Oro. Replace 5% of wheat flour banana. Banana flour has less calories and Trans fats, more fiber and complex carbohydrate, which is important for diabetics“, vitamins and minerals. The new ingredient is a flavor and nutritional intake. By adding banana flour, elasticity is lost due to reduced wheat gluten, so should knead longer. After baking, the bread crumb took a similar grain bread color, and the aroma is minimal and the taste is delicious, which does not affect the. for consumer tastes make bread under these conditions, ingredients: 450 g wheat flour, 50 g of banana flour, 10 g salt, 10 g of dry yeast, 40 g butter, 2 eggs, 500 ml water, and the preparation is to dissolve the yeast in the liquid, then gather all the ingredients and knead, getting 20 breads that are made with the mixture reach the desired texture and flavor.